Adhesive composition, connected structure and method for producing same
By using an adhesive composition containing conductive particles and a nitrogen-containing aromatic heterocycle between the circuit members, the problem of rising metal electrode connection resistance is solved, and a high reliability connection structure is achieved.
Patent Information
- Application Number
- CN202411361143.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-01-17
- Filing Date
- 2019-01-15
- Publication Date
- 2025-01-03
AI Technical Summary
When using metal electrodes with low surface resistance, the connection resistance of the existing adhesive film is prone to rise, which affects the connection reliability.
The adhesive composition containing conductive particles and a nitrogen-containing aromatic heterocycle is used to cure the adhesive composition by placing the circuit members and pressurized heating to form a connecting structure.
The increase in the connection resistance is effectively suppressed, the connection reliability is improved, and an excellent connection structure and its manufacturing method are provided.
Smart Images

Figure CN119242209A_ABST
Abstract
Description
[0001] The present invention is a divisional application of the invention application with application number 201980007769.7 (international application number PCT / JP2019 / 000954), application date January 15, 2019, and invention name “Adhesive composition, connection structure and manufacturing method thereof”. Technical Field
[0002] The present invention relates to an adhesive composition, a connection structure and a method for producing the same. Background Art
[0003] In recent years, the miniaturization, thinning and high performance of electronic components have been continuously promoted. At the same time, the development of economical high-density mounting technology is actively carried out. It is difficult to connect electronic components with fine circuit electrodes to circuit components through conventional solder and rubber connectors. Therefore, most of the connection methods disclosed in patent documents 1 to 6, which utilize anisotropic conductive adhesive compositions and their films (adhesive films) with excellent decomposition ability, are used. For example, when connecting the glass of a liquid crystal display (Liquid Crystal Display) to a circuit component such as TAB (Tape Automated Bonding) or FPC (Flexible Print Circuit), an anisotropic conductive adhesive film containing conductive particles is clamped between the relative electrodes, and heated and pressurized, thereby maintaining the insulation between adjacent electrodes on the same substrate while electrically connecting the electrodes of the two substrates to each other, thereby crimping and fixing the electronic components with fine circuit electrodes to the circuit components.
[0004] In addition, modules are required to be lightweight, thin, and highly sensitive. In display modules such as liquid crystal display devices and electronic paper, or sensor substrates such as touch panels, copper, gold, aluminum, and their alloys with low surface resistance are used as electrodes instead of the conventional silver paste to reduce wiring resistance, thereby narrowing the wiring width and reducing wiring resistance. In anisotropic conductive adhesive films, research has also been conducted on optimizing the raw materials contained in the adhesive film in order to reduce connection resistance.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 08-148213
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 08-124613
[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 11-50032
[0010] Patent Document 4: Japanese Patent Application Publication No. 2011-91044
[0011] Patent Document 5: Japanese Patent Application Publication No. 2011-100605
[0012] Patent Document 6: Japanese Patent Application Publication No. 2013-55058 Summary of the invention
[0013] Problems to be solved by the invention
[0014] Among the metals with low surface resistance, research has been conducted on using easily available copper, copper alloys, copper oxides, etc. for electrodes. However, when conventional adhesive films are applied to such electrodes, for example, the connection resistance sometimes increases over time, and there is room for further improvement in connection reliability.
[0015] Therefore, an object of the present invention is to provide an adhesive composition capable of suppressing an increase in connection resistance and improving connection reliability. Another object of the present invention is to provide a connection structure having excellent connection reliability and a method for producing the same.
[0016] Methods for solving problems
[0017] One aspect of the present invention is an adhesive composition including conductive particles and a compound having a nitrogen-containing aromatic heterocyclic ring.
[0018] The nitrogen-containing aromatic heterocyclic ring is preferably selected from a pyrazole ring, an imidazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring, At least one of the group consisting of an azole ring and a pyrimidine ring. Thus, the connection reliability can be further improved.
[0019] The adhesive composition is preferably used to connect circuit members to each other.
[0020] Another aspect of the present invention is a connection structure, which comprises: a first circuit component, which has a first substrate and a first electrode provided on the first substrate; a second circuit component, which has a second substrate and a second electrode provided on the second substrate; and a circuit connecting component, which is arranged between the first circuit component and the second circuit component and electrically connects the first electrode and the second electrode to each other; the circuit connecting component is a cured product of the above-mentioned adhesive composition.
[0021] The first electrode and the second electrode are preferably copper, a copper alloy, or copper oxide.
[0022] Another aspect of the present invention is a method for manufacturing a connection structure, which comprises the following steps: disposing the above-mentioned adhesive composition between a first circuit member and a second circuit member, the first circuit member having a first substrate and a first electrode provided on the first substrate, and the second circuit member having a second substrate and a second electrode provided on the second substrate; and crimping the first circuit member and the second circuit member via the above-mentioned adhesive composition, thereby electrically connecting the first circuit member and the second circuit member.
[0023] Effects of the Invention
[0024] According to the present invention, an adhesive composition capable of suppressing an increase in connection resistance and improving connection reliability can be provided. In addition, the present invention can provide a connection structure having excellent connection reliability and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic cross-sectional view showing an adhesive film according to one embodiment.
[0026] Figure 2 This is a schematic cross-sectional view showing a method for producing a connection structure according to one embodiment.
[0027] Figure 3 This is a schematic cross-sectional view showing a copper electrode film adhered body used in Examples. DETAILED DESCRIPTION
[0028] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.
[0029] An adhesive composition according to one embodiment includes an adhesive component and conductive particles dispersed in the adhesive component. The adhesive component is defined as a non-volatile component in the adhesive composition excluding the conductive particles.
[0030] The conductive particles include, for example, polymer particles (plastic particles) such as polystyrene, and a metal layer covering the polymer particles. The polymer particles are preferably substantially entirely covered with a metal layer on their surface, but a portion of the polymer particle surface may be exposed without being covered with a metal layer within a range that allows the function as a circuit connection material to be maintained. The polymer particles may also be particles containing, for example, a polymer containing at least one monomer selected from styrene and divinylbenzene as a monomer unit.
[0031] The average particle size of the polymer particles may preferably be greater than or equal to 1 μm, may be less than or equal to 40 μm, or may be 1 to 40 μm. From the viewpoint of high-density installation, the average particle size of the polymer particles may more preferably be less than or equal to 30 μm, or may be 1 to 30 μm. From the viewpoint of maintaining the connection state more stably even when the surface of the electrode has unevenness, the average particle size of the polymer particles may further preferably be greater than or equal to 2 μm, may be less than or equal to 20 μm, or may be 2 to 20 μm. The average particle size of the polymer particles can be observed using a scanning electron microscope (SEM), and the particle sizes of 300 polymer particles are measured to obtain the average value thereof.
[0032] The metal layer can be formed of various metals such as Ni, Ni / Au, Ni / Pd, Cu, NiB, Ag, Ru, etc. The metal layer may be a thin film produced by plating, vapor deposition, sputtering, etc.
[0033] From the viewpoint of improving insulation, the conductive particles may further include an insulating layer provided outside the metal layer and covering the metal layer. The insulating layer may be a layer formed of an insulating material such as silicon dioxide or acrylic acid.
[0034] The conductive particles preferably have a surface on which a plurality of protrusions are formed. The conductive particles having protrusions can be obtained, for example, by forming a metal layer on the surface of polymer particles by metal plating.
[0035] The content of the conductive particles is determined according to the fineness of the electrodes to be connected, etc. For example, the content of the conductive particles may be greater than or equal to 1 part by volume, less than or equal to 50 parts by volume, or 1 to 50 parts by volume relative to 100 parts by volume of the adhesive component. From the viewpoint of insulation and manufacturing cost, the content of the conductive particles may more preferably be less than or equal to 30 parts by volume, or 1 to 30 parts by volume relative to 100 parts by volume of the adhesive component.
[0036] In one embodiment, the adhesive component contains a radical polymerizable substance having insulating properties and curing by heat or light, a free radical generator, and a compound having a nitrogen-containing aromatic heterocyclic ring.
[0037] The free radical polymerizable substance is a substance having a functional group that polymerizes by free radicals, and examples thereof include acrylate compounds, methacrylate compounds, and maleimide compounds. The content of the free radical polymerizable substance may be, for example, greater than or equal to 50% by mass, less than or equal to 80% by mass, or 50 to 80% by mass, based on the total amount of the adhesive component.
[0038] Examples of acrylate compounds and methacrylate compounds include urethane acrylate, urethane methacrylate, methyl acrylate, ethyl acrylate, isopropyl acrylate, isobutyl acrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, dimethylol tricyclodecane diacrylate, trimethylol propane triacrylate, tetramethylol methane tetraacrylate, 2-hydroxy-1,3-diacryloxy propane, 2,2-bis[4-(acryloyloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloyloxypolyethoxy)phenyl]propane, dicyclopentenyl acrylate, tricyclodecyl acrylate, bis(acryloyloxyethyl)isocyanurate, ε-caprolactone-modified tri(acryloyloxyethyl)isocyanurate, and tri(acryloyloxyethyl)isocyanurate. The radical polymerizable substance may be used alone or in combination of two or more thereof. From the viewpoint of adhesiveness, the radical polymerizable substance is preferably urethane acrylate or urethane methacrylate.
[0039] As the radical polymerizable substance, from the viewpoint of improving heat resistance, it is particularly preferred to use urethane acrylate or urethane methacrylate in combination with a radical polymerizable substance that independently exhibits a Tg of 100° C. or higher when crosslinked with an organic peroxide. Such a radical polymerizable substance may be a compound having a dicyclopentenyl group and / or a tricyclodecanyl group, and is preferably a compound having a tricyclodecanyl group.
[0040] The viscosity of the radical polymerizable substance at 25° C. may be greater than or equal to 100,000 mPa·s, less than or equal to 1,000,000 mPa·s, or 100,000 to 1,000,000 mPa·s, preferably less than or equal to 500,000 mPa·s, or 100,000 to 500,000 mPa·s. The viscosity of the radical polymerizable substance at 25° C. can be measured using a commercially available E-type viscometer.
[0041] The free radical generator is a compound that generates free radicals by decomposition by heat or light, such as a peroxide compound or an azo compound. The free radical generator is appropriately selected according to the target connection temperature, connection time, pot life, etc. The free radical generator can be, for example, one or more selected from benzoyl peroxide, diacyl peroxide, peroxydicarbonate, peroxyester, peroxyketal, dialkyl peroxide and hydroperoxide. From the viewpoint of high reactivity and pot life, the free radical generator is preferably an organic peroxide compound with a half-life of 10 hours at a temperature greater than or equal to 40°C and a half-life of 1 minute at a temperature less than or equal to 180°C. Based on the total amount of the adhesive component, the content of the free radical generator can be, for example, greater than or equal to 0.05% by mass, less than or equal to 15% by mass, or 0.05 to 15% by mass. In the case where the adhesive component contains a free radical generator, the free radical generator can also be used in combination with a decomposition promoter, an inhibitor, etc.
[0042] The adhesive component of the present embodiment may further include a polymerization inhibitor. The polymerization inhibitor may be a hydroquinone compound, a methyl ether hydroquinone compound, etc. Based on the total amount of the adhesive component, the content of the polymerization inhibitor may be greater than or equal to 0.05 mass %, less than or equal to 5 mass %, or 0.05 to 5 mass %.
[0043] A compound having a nitrogen-containing aromatic heterocycle (hereinafter also referred to as a "heterocyclic compound") is a compound having an aromatic heterocycle containing one or more nitrogen atoms in the ring. The nitrogen-containing aromatic heterocycle (hereinafter also referred to as a "heterocycle") is composed of at least two types of atoms, carbon atoms and nitrogen atoms, and may also be composed of three or more types of atoms including other atoms such as sulfur atoms and oxygen atoms in addition to carbon atoms and nitrogen atoms. The heterocycle contains, for example, 1 to 4 nitrogen atoms, preferably 2 to 4 nitrogen atoms. When the nitrogen atom contained in the heterocycle is one, the heterocycle preferably further contains the above-mentioned other atoms in addition to carbon atoms and nitrogen atoms.
[0044] The heterocyclic ring is preferably a compound having a 5-membered ring or a 6-membered ring, and more preferably a compound having a 5-membered ring (azole). Examples of the 5-membered ring include a pyrazole ring, an imidazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring, Examples of the 6-membered ring include a pyrimidine ring and the like.
[0045] From the viewpoint of suppressing the increase of connection resistance and further improving connection reliability, the heterocyclic ring is preferably selected from a pyrazole ring, an imidazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring, At least one of the group consisting of an azole ring and a pyrimidine ring, more preferably selected from a pyrazole ring, an imidazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring and The at least one member selected from the group consisting of azole rings is more preferably at least one member selected from the group consisting of triazole rings, tetrazole rings and thiadiazole rings.
[0046] The heterocyclic ring may be unsubstituted or may have a substituent (the hydrogen atom bonded to the atom constituting the heterocyclic ring is substituted). In the case where the heterocyclic ring has a substituent, the substituent may be a hydrocarbon group or an organic group containing a sulfur atom, an oxygen atom, etc. The hydrocarbon group may be an alkyl group, etc. The organic group containing a nitrogen atom may be an amino group, etc. The organic group containing a sulfur atom may be a mercapto group, etc.
[0047] The heterocyclic compound may have a nitrogen-containing aromatic heterocyclic ring including a monocyclic ring, or may have a polycyclic ring formed by condensation of an aromatic ring composed only of hydrocarbons (e.g., a substituted or unsubstituted benzene ring) and the above-mentioned nitrogen-containing aromatic heterocyclic ring. Such a polycyclic ring may be, for example, a benzimidazole ring, a benzotriazole ring, a benzothiazole ring, a benzo Azole ring, etc.
[0048] Specifically, the heterocyclic compound can be 5-methyltetrazole, 5-amino-1H-tetrazole, 3-mercapto-1,2,4-triazole, benzotriazole, 2-aminopyrimidine, 5,6-dimethylbenzimidazole, 2-amino-5-mercapto-1,3,4-thiadiazole, 2-mercaptopyrimidine, 2-mercaptobenzotriazole, azole, 2-mercaptobenzothiazole, 2-mercaptobenzimidazole, etc.
[0049] From the viewpoint of suppressing the increase in connection resistance and further improving connection reliability, the content of the heterocyclic compound is preferably greater than or equal to 0.01 parts by volume, more preferably greater than or equal to 0.1 parts by volume, and further preferably greater than or equal to 0.2 parts by volume, relative to 100 parts by volume of the adhesive component. In addition, it is preferably less than or equal to 5 parts by volume, more preferably less than or equal to 2 parts by volume, and further preferably less than or equal to 1 part by volume.
[0050] In another embodiment, the adhesive component contains a thermosetting resin and the above-mentioned compound having a nitrogen-containing aromatic heterocyclic ring.
[0051] Thermosetting resins include, for example, epoxy resins, cyanate resins, maleimide resins, allyl nadic imide resins, phenolic resins, urea resins, alkyd resins, acrylic resins, unsaturated polyester resins, diallyl phthalate resins, silicone resins, resorcinol formaldehyde resins, xylene resins, furan resins, polyurethane resins, ketone resins, triallyl cyanurate resins, polyisocyanate resins, resins containing tris(2-hydroxyethyl)isocyanurate, resins containing triallyl trimellitate, thermosetting resins synthesized from cyclopentadiene, thermosetting resins obtained by trimerization of aromatic dicyanamide, etc. Thermosetting resins can be used alone or in combination of two or more. Based on the total amount of the adhesive component, the content of the thermosetting resin can be, for example, greater than or equal to 20% by mass, less than or equal to 50% by mass, or 20 to 50% by mass.
[0052] In the case where the adhesive component contains a thermosetting resin, the adhesive component may further contain a curing agent. The curing agent may be, for example, a catalyst-type curing agent. The catalyst-type curing agent may be hydrazide, boron trifluoride-amine complex, sulfonium salt, amine imide, diaminomaleonitrile, polyamine salt, dicyandiamide, etc., or may be a modified substance thereof. The curing agent may also be an addition-type curing agent such as polyamine, polythiol, polyphenol, acid anhydride, etc. As a curing agent, an addition-type curing agent and a catalyst-type curing agent may also be used in combination. The curing agent may be used alone or in combination of two or more. Based on the total amount of the adhesive component, the content of the curing agent may be greater than or equal to 0.5% by mass, may be less than or equal to 15% by mass, or may be 0.5 to 15% by mass.
[0053] The curing agent may be a material obtained by coating the above curing agent with a polymer compound such as polyurethane or polyester, or a metal thin film such as Ni or Cu, or an inorganic compound such as calcium silicate, and then microencapsulating the above curing agent. Such a curing agent is preferred because it can prolong the usable time.
[0054] In another embodiment, the adhesive component contains the above-mentioned radical polymerizable substance, a free radical generator, a thermosetting resin, and a compound having a nitrogen-containing aromatic heterocyclic ring.
[0055] In the present embodiment, the total content of the radical polymerizable substance and the content of the thermosetting resin may be, for example, greater than or equal to 50 mass %, less than or equal to 80 mass %, or 50 to 80 mass % based on the total amount of the adhesive component.
[0056] In each of the above-mentioned embodiments, the adhesive component may further contain fillers such as silicone particles, softeners, accelerators, antioxidants, colorants, flame retardants, thixotropic agents, coupling agents, and the like.
[0057] The adhesive composition may be in a paste state, but may preferably be an adhesive film formed into a film state from the viewpoint of workability. Figure 1 Schematic cross-sectional view showing a film-like adhesive composition (adhesive film) according to one embodiment. Figure 1 As shown, in one embodiment, the adhesive film 1 is composed of a layer including an adhesive component 2 and conductive particles 3 dispersed in the adhesive component 2. In one embodiment, the adhesive component 2 and the conductive particles 3 may also be the above-mentioned adhesive component and conductive particles. The thickness of the adhesive film 1 may be, for example, greater than or equal to 10 μm, less than or equal to 50 μm, or 10 to 50 μm.
[0058] In the case where the adhesive composition is formed into a film, in order to improve film formation, the adhesive component can also include insulating resins other than the above-mentioned thermosetting resins. As insulating resins, polystyrene, polyethylene, polyvinyl butyral, polyvinyl formal, polyimide, polyamide, polyvinyl chloride, polyphenylene ether, urea resin, phenoxy resin, polyimide resin, polyester polyurethane resin, etc. can be used. From the viewpoint of further improving connection reliability, it can also be a high molecular weight phenoxy resin with a weight average molecular weight greater than or equal to 10000 obtained by high performance liquid chromatography (HPLC). The adhesive component can also contain substances modified by these resins with free radical polymerizable functional groups, and in order to adjust melt viscosity, etc., it can also contain a mixture of these resins and styrene resins or acrylic resins. As another embodiment, in order to improve film formation, the adhesive component can also contain rubber.
[0059] The adhesive film may also be a multilayer structure. The adhesive film may be, for example, a two-layer structure consisting of a layer containing conductive particles and a layer not containing conductive particles, or a three-layer structure consisting of a layer containing conductive particles and a layer not containing conductive particles disposed on both sides thereof. A plurality of layers containing conductive particles may also be provided in the adhesive film. These multilayer adhesive films can efficiently configure conductive particles on electrodes, and are therefore suitable for narrow pitch connection. In consideration of adhesion to circuit components, the adhesive film may further have an adhesive layer showing high adhesion relative to each circuit component to be connected.
[0060] The adhesive composition (adhesive film) described above can be suitably used as a material (circuit connecting material) for connecting circuit members to each other, and can be particularly suitably used as an anisotropic conductive adhesive composition (anisotropic conductive adhesive film) for connecting circuit members to each other.
[0061] Next, a method for producing a connection structure using the adhesive film 1 will be described. Figure 21 is a schematic cross-sectional view showing a method for manufacturing a connection structure according to one embodiment. Figure 2 As shown in (a), a first circuit member 6 including a first substrate 4 and a first electrode 5 provided on the first substrate 4, and a second circuit member 9 including a second substrate 7 and a second electrode 8 provided on the second substrate 7 are prepared.
[0062] Next, the first circuit member 6 and the second circuit member 9 are arranged so that the first electrode 5 and the second electrode 8 face each other, and the adhesive film 1 is arranged between the first circuit member 6 and the second circuit member 9 .
[0063] Then, the adhesive film 1 is cured while the entirety is pressurized in the directions of arrows A and B. The pressure during pressurization can be, for example, 1 to 10 MPa relative to the total connection area. The method for curing the adhesive film 1 can be a method utilizing heating, or a method utilizing light irradiation in addition to heating. Heating can be performed, for example, at 100 to 170° C. Pressurization and heating (light irradiation as needed) can be performed, for example, for 1 to 160 seconds. Thus, the first circuit member 6 and the second circuit member 9 are crimped together via the cured product of the adhesive composition constituting the adhesive film 1.
[0064] In this embodiment, the adhesive film 1 is disposed between the first circuit member 6 and the second circuit member 9. As another embodiment, a paste adhesive composition may be applied to the first circuit member 6 or the second circuit member 9 or both instead of the adhesive film.
[0065] like Figure 2 As shown in (b), a connection structure 11 according to one embodiment obtained in the above manner comprises: a first circuit member 6 having a first substrate 4 and a first electrode 5 provided on the first substrate 4; a second circuit member 9 having a second substrate 7 and a second electrode 8 provided on the second substrate 7; and a circuit connection member 10, which is arranged between the first circuit member 6 and the second circuit member 9 and electrically connects the first electrode 5 and the second electrode 8 to each other. The circuit connection member 10 is composed of a cured product of an adhesive composition, and includes a cured product 12 of an adhesive component 2, and conductive particles 3 dispersed in the cured product 12. In the connection structure 11, the first electrode 5 and the second electrode 8 are electrically connected to each other by the conductive particles 3 interposed between them.
[0066] The first substrate 4 and the second substrate 7 may be the same as or different from each other, and may be, for example, a flexible substrate including a thermoplastic resin, a glass substrate, or a composite substrate including a glass substrate and an insulating film provided on the glass substrate.
[0067] The flexible substrate may be, for example, an organic substrate formed of an organic material including at least one thermoplastic resin selected from the group consisting of polyimide (PI), polyethylene terephthalate (PET), polycarbonate (PC), and polyethylene naphthalate (PEN).
[0068] The flexible substrate may further have a modified treatment film and / or protective film formed on the surface of the organic substrate for improving optical and mechanical properties, such as a hard coating. In order to facilitate the handling and transportation of the flexible substrate, a reinforcing material selected from glass material and SUS may be attached to the organic substrate.
[0069] From the perspective of ensuring the strength of the film and ease of bending through the substrate alone, the thickness of the flexible substrate is preferably greater than or equal to 10 μm, less than or equal to 200 μm, or 10 to 200 μm, more preferably less than or equal to 125 μm, or 10 to 125 μm.
[0070] If conventional circuit connection materials are used, the electrodes on the flexible substrate may be broken or cracked due to the heating and pressurization for crimping the circuit components. In addition, for the connection of electrodes that are difficult to form a sufficient electrical connection, the circuit components must be crimped under conditions of lower temperature or lower stress in order to suppress the breakage of the electrodes. The adhesive film 1 of this embodiment can have advantageous effects in these aspects compared to conventional materials.
[0071] The glass substrate may be formed of soda glass, quartz glass, etc. From the viewpoint of preventing damage caused by external stress, a chemical strengthening treatment may be applied to the substrate formed of these materials. The composite substrate may have a glass substrate and an insulating film provided on the surface of the glass substrate, the insulating film being composed of polyimide or an organic material or inorganic material for decorative coloring. In the composite substrate, the electrode may be formed on the insulating film.
[0072] As a combination of the first substrate 4 and the second substrate 7, more specifically, the first substrate 4 can be an IC chip or a flexible substrate containing a thermoplastic resin, and the second substrate 7 can be a flexible substrate containing a thermoplastic resin. Alternatively, the first substrate 4 can be an IC chip or a flexible substrate, and the second substrate 7 can be a glass substrate or a composite substrate. In other words, when the second substrate 7 is a flexible substrate, the first substrate 4 can be an IC chip or a flexible substrate. When the first substrate 4 is an IC chip and the second substrate 7 is a flexible substrate, the above-mentioned adhesive film 1 can be used for COP (Chip on Plastic substrate) connection. When the first substrate 4 and the second substrate 7 are flexible substrates, the above-mentioned adhesive film 1 can be used for FOP (Film on Plastic substrate) connection.
[0073] When the second substrate 7 is a flexible substrate, the first circuit member 6 may be an electronic component such as a semiconductor chip, an active element such as a transistor, a diode, a thyristor, a capacitor, a resistor, a coil, or the like, a printed circuit board, or a glass substrate on which a circuit such as ITO is formed. When the first substrate 4 is a semiconductor chip or a glass substrate, a bump formed by plating or the tip of a gold wire may be melted by a welding gun or the like to form a gold ball, and the ball may be crimped onto an electrode sheet, and a protruding electrode such as a wire bump obtained by cutting the wire may be provided, thereby using the first circuit member 6.
[0074] As electrode materials for forming the first electrode 5 and the second electrode 8, metals such as Ag, Ni, Al, Au, Cu, Ti, and Mo and transparent conductors such as ITO, IZO, silver nanowires, and carbon nanotubes can be listed. The first electrode 5 and the second electrode 8 can be formed of the same material or different materials, but are preferably formed of the same material. From the viewpoint of reducing connection resistance and ease of acquisition, the first electrode 5 and the second electrode 8 are preferably formed of copper, a copper alloy, or copper oxide. From the viewpoint of preventing disconnection, a surface layer such as an oxide or nitride film, an alloy film, an organic film, etc. can also be further provided on the first electrode 5 and the second electrode 8. The first electrode 5 and the second electrode 8 can also be provided one by one on the first circuit member 6 and the second circuit member 9, respectively, but it is preferred to provide a plurality of first electrodes 5 and the second electrode 8 at predetermined intervals.
[0075] Example
[0076] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0077] <Example 1>
[0078] 20 parts by mass of urethane acrylate (product name: UA-5500T, manufactured by Shin-Nakamura Chemical Co., Ltd.) as a radical polymerizable substance, 15 parts by mass of bis(acryloyloxyethyl)isocyanurate (product name: M-215, manufactured by Toagosei Co., Ltd.), 5 parts by mass of dimethyloltricyclodecane diacrylate (product name: DCP-A, manufactured by Kyoeisha Chemical Co., Ltd.), 1 part by mass of 2-methacryloyloxyethyl acid phosphate (product name: P-2M, manufactured by Kyoeisha Chemical Co., Ltd.), 8 parts by mass of benzoyl peroxide (product name: Nyper BMT-K, manufactured by NOF Corporation) as a free radical generator, and 60 parts by mass of a solution containing a polyester polyurethane resin (product name: UR4800, manufactured by Toyobo Co., Ltd.) as an insulating resin at a concentration of 40% were mixed and stirred to obtain a resin solution. At this time, the polyester polyurethane resin solution is prepared by dissolving the polyester polyurethane resin in a mixed solvent of toluene / methyl ethyl ketone = 50 / 50.
[0079] On the other hand, a nickel layer with a thickness of 0.2 μm is formed on the surface of the polystyrene particles. Further, a gold layer with a thickness of 0.04 μm is formed on the outside of the nickel layer. Thus, conductive particles with an average particle size of 4 μm are prepared. The conductive particles are dispersed in the modulated resin solution at a ratio of 10 parts by volume relative to 100 parts by volume of the resin solution. 5-methyltetrazole is dispersed therein at a ratio of 1 part by volume relative to 100 parts by volume of the resin solution. Further, silicone particles with an average particle size of 2 μm as a filler (product name: KMP-605, manufactured by Shin-Etsu Chemical Co., Ltd.) are dispersed at a ratio of 20 parts by mass relative to 100 parts by mass of the resin solution to obtain a coating liquid of an adhesive composition comprising a free radical polymerizable substance, a free radical generator, an insulating resin, conductive particles, a compound having a nitrogen-containing aromatic heterocycle, and a filler. The coating liquid is applied to a polyethylene terephthalate (PET) film (thickness 50 μm) with a demolding treatment performed on one side using a coating device. The coating film was dried by hot air drying at 70° C., thereby forming an anisotropic conductive adhesive film (18 μm thick) containing the adhesive composition according to Example 1.
[0080] <Examples 2 to 5, Comparative Example 1>
[0081] Adhesive films according to Examples 2 to 5 were prepared in the same manner as in Example 1, except that the compound having a nitrogen-containing aromatic heterocycle shown in Table 1 was used instead of 5-methyltetrazole in Example 1. In addition, an adhesive film according to Comparative Example 1 was prepared in the same manner as in Example 1, except that 5-methyltetrazole was not added in Example 1.
[0082] <Production of copper electrode film attached body>
[0083] As an adherend modeled after a circuit member, a copper electrode film member having a PET film and a copper film formed on the PET film was prepared. On the copper film of the copper electrode film member, the produced adhesive film was heated so that the adhesive film reached a temperature of 70° C., and the entirety was pressurized for 10 seconds at a pressure of 2 MPa relative to the total connection area, thereby obtaining a copper electrode film attached body having a cured product of an adhesive composition derived from the adhesive film. Figure 3 Schematic cross-sectional view showing a copper electrode film attached body. Figure 3 As shown, in the copper electrode film attached body 13, a copper film 15 is formed on a PET film 14, and a cured product 20 of an adhesive composition (including a cured product 22 of an adhesive component and conductive particles 23) is further provided on a surface 15a of the copper film 15 opposite to the PET film 14.
[0084] <Evaluation of connection reliability>
[0085] The obtained attached bodies of Examples 1 to 5 and Comparative Example 1 were left to stand for 100 hours in an environment of 85°C and 85% RH and then subjected to reliability testing. Regarding the copper electrode film attached body 13 before and after the test, the appearance of the portion (attached portion) in contact with the cured product 20 in the surface 15a of the copper film 15 on the opposite side of the PET film 14 was visually observed. The connection reliability was evaluated by setting A as the case where almost no discoloration was observed before and after the test, B as the case where discoloration was observed but to a small extent, and C as the case where severe discoloration was observed. The evaluation results are shown in Table 1. If the evaluation result is A or B, it can be said that the connection reliability is excellent.
[0086] <Evaluation of connection resistance>
[0087] After the obtained anisotropic conductive adhesive films of Examples 1 to 5 and Comparative Example 1 were attached to the copper electrode film, a flexible circuit board (FPC) was placed on the adhesive film on the opposite side of the copper electrode film, and the adhesive film was heated in such a way that the temperature reached was 170°C, and the whole was pressurized for 10 seconds at a pressure of 2 MPa relative to the total connection area, thereby obtaining an adhesive film assembly a (connection structure). As a flexible circuit substrate, a substrate with an electrode width of 150 μm, an inter-electrode spacer of 150 μm, an inter-electrode pitch of 300 μm, a copper foil thickness of 18 μm, and Ni (film thickness 3 μm) and Au (film thickness 0.01 μm) formed on the surface was used. The adhesive film assembly a was subjected to a reliability test after being left to stand for 100 hours in an environment of 85°C and 85% RH. The connection resistance of the adhesive film assembly a after the reliability test was measured, and the case of 1Ω or less was evaluated as A, and the case of more than 1Ω was evaluated as B. As shown in Table 1, the connection resistance of the adhesive film assembly a of Examples 1 to 5 was all 1Ω or less, which was good.
[0088] <Evaluation of Adhesion>
[0089] After the obtained anisotropic conductive adhesive films of Examples 1 to 5 and Comparative Example 1 were attached to a PET film having a SiO2 film, a flexible circuit board (FPC) was placed on the adhesive film on the opposite side of the PET film, and the adhesive film was heated in such a way that the reaching temperature became 170°C, and the whole was pressed for 10 seconds at a pressure of 2 MPa relative to the total connection area, thereby obtaining an adhesive film assembly b (connection structure). As a flexible circuit board, a substrate with an electrode width of 150 μm, an electrode spacing of 150 μm, an electrode spacing of 300 μm, a copper foil thickness of 18 μm, and Ni (film thickness 3 μm) and Au (film thickness 0.01 μm) formed on the surface was used. The adhesive film assembly b was left to stand for 100 hours in an environment of 85°C and 85% RH and then subjected to a reliability test. The adhesiveness (adhesive force) of the adhesive film mounted body b after the reliability test was measured, and the case of 4 N / cm or more was evaluated as A, and the case of less than 4 N / cm was evaluated as B. As shown in Table 1, the adhesive force was 4 N / cm or more in all cases, which was good.
[0090] [Table 1]
[0091]
[0092] Explanation of symbols
[0093] 1: adhesive film (adhesive composition), 2: adhesive component, 3: conductive particles, 4: first substrate, 5: first electrode, 6: first circuit member, 7: second substrate, 8: second electrode, 9: second circuit member, 10: circuit connecting member (cured product of the adhesive composition), 11: connecting structure.
Claims
1. An adhesive composition comprising conductive particles and an adhesive component, wherein the adhesive component comprises a compound having a nitrogen-containing aromatic heterocyclic ring, The adhesive component contains a free radical polymerizable substance, The radical polymerizable substance contains urethane acrylate or urethane methacrylate. 2 . The adhesive composition according to claim 1 , wherein the adhesive component further comprises a radical polymerizable substance which independently exhibits a Tg of 100° C. or higher when cross-linked by an organic peroxide. The adhesive composition according to claim 1 , wherein the nitrogen-containing aromatic heterocyclic ring comprises a single ring.
4. The adhesive composition according to claim 1, wherein the nitrogen-containing aromatic heterocyclic ring is selected from the group consisting of a pyrazole ring, an imidazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring, At least one of the group consisting of an azole ring and a pyrimidine ring.
5. The adhesive composition according to claim 1 or 2, which is used for connecting circuit members to each other.
6. A connection structure comprising: A first circuit member having a first substrate and a first electrode disposed on the first substrate; A second circuit member having a second substrate and a second electrode disposed on the second substrate; as well as a circuit connecting member disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other; The circuit-connecting member is a cured product of the adhesive composition according to any one of claims 1 to 5. 7 . The connection structure according to claim 6 , wherein the first electrode and the second electrode are formed of copper, a copper alloy, or a copper oxide.
8. A method for manufacturing a connection structure, comprising the following steps: The adhesive composition according to any one of claims 1 to 5 is disposed between a first circuit member and a second circuit member, wherein the first circuit member has a first substrate and a first electrode provided on the first substrate, and the second circuit member has a second substrate and a second electrode provided on the second substrate; The first circuit member and the second circuit member are crimped together via the adhesive composition to electrically connect the first circuit member and the second circuit member to each other.
